2002
DOI: 10.1002/da.10060
|View full text |Cite
|
Sign up to set email alerts
|

Replication and expansion of findings related to racial differences in veterans with combat-related PTSD

Abstract: Racial differences in those seeking treatment at a Veterans Affairs Medical Center (VAMC) outpatient posttraumatic stress disorder (PTSD) treatment program were examined. One hundred eleven (71 Caucasian and 40 African American) veterans were compared on both self-report measures and interview measures of PTSD, depression, dissociation, and general psychopathology. Participants completed the following self-report measures: the Beck Depression Inventory, the Dissociative Experiences Scale, the Mississippi Comba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 27 publications
8
34
0
Order By: Relevance
“…Several earlier studies have shown that significantly more African American than Caucasian veterans demonstrate PTSD in southern populations of combat veterans, as reviewed by Frueh et al [1998]. In an extensive analysis of the effects of race on PTSD severity and symptomology, these same investigators found that race had little effect on these variables [Frueh et al, 1997;Monnier et al, 2002]. Results of this study support these conclusions.…”
Section: Discussionsupporting
confidence: 79%
“…Several earlier studies have shown that significantly more African American than Caucasian veterans demonstrate PTSD in southern populations of combat veterans, as reviewed by Frueh et al [1998]. In an extensive analysis of the effects of race on PTSD severity and symptomology, these same investigators found that race had little effect on these variables [Frueh et al, 1997;Monnier et al, 2002]. Results of this study support these conclusions.…”
Section: Discussionsupporting
confidence: 79%
“…In their review of the empirical literature examining this association, however, Frueh, Brady, & Arellano (1998) contend that the results of past studies are anything but clear. They conclude that both the limited amount of research and the inconsistent empirical data pertaining to race and PTSD prevented any definitive conclusions about the role of race/ethnicity in understanding differences in PTSD rates (Frueh et al 1998;Monnier et al 2002). Our results do support other analyses of community samples and the finding of no racial and ethnic differences in PTSD (e.g., Kessler et al 1995).…”
Section: Discussionsupporting
confidence: 77%
“…Some researchers have found that racial and ethnic minorities, primarily African Americans, suffer from higher rates of psychological disorders compared to Whites (Galea et al 2002;Warheit, Holzer, & Arey 1975). In contrast, other researchers have discovered few differences between racial and ethnic groups for psychological problems, once background and stress exposure factors have been controlled (Breslau et al 1998;Galea et al 2003;Kessler, Sonnega, Bromet, & Hughes, 1995;Monnier, Elhai, Frueh, Sauvageot, & Magruder 2002), or that African Americans may in fact have lower rates of depression relative to other groups (e.g., Kessler et al 2003). In most of these studies, though, minority participants reported more negative life events compared to their White counterparts (see also Turner, Taylor & Van Gundy 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 9/ 11 study, the cross-cultural conflict could heighten the crisis effect on the vulnerable minorities (Galea et al, 2002;Khaylis et al, 2007), and minorities then reported higher levels of PTSD symptoms (Ai et al, 2010). Monnier, Elhai, Frueh, Sauvageot, and Magruder (2002), however, found no Black-versus-White racial differences in symptom improvement in their prospective assessment of 403 veterans with longstanding, severe war-related PTSD. The mixed findings suggested the potential impact of contextual factors (e.g., the political nature of events, common goals across races) should be taken into account in examining racial differences in traumatization.…”
Section: Risk Factors As Previous Trauma Trauma Stressors and Negatmentioning
confidence: 92%